Calculation of stationary points in linear bilevel programming problems - D. E. Berezhnov; L. I. Minchenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Bilevel programming problems are considerably difficult for numerical analysis. Despite the vast amount of literature and research dedicated to studying them, there are no universal methods to solve them and numerous publications are concerned mainly with identifying particular subsets of problems that can be efficiently analyzed. Linear bilevel programming problems are considered, and an algorithm for computing their stationary points is developed in this paper.